Greco-Roman precedents on Confederate currency = Grecko-rzymskie pierwowzory środków płatniczych Konfederacji - Győri, Victoria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper examines why and how, during the period of the American Civil War, the Southern Confederacy modelled itself on the ideals of the Greco-Roman world. One of the best ways to exemplify the link between the Old South and the classical antiquity is to analyze the banknotes and coins of the Treasury of the Confederate States of America. Confederate currency demonstrates the significant impact Greece and Rome had on the values, ideals, and society that the Old South founded itself on.
Keywords: American Civil War; Confederate States of America; U.S. banknotes and coins; Greek and Roman coins; virtue; Stany Zjednoczone Ameryki Północnej; wojna secesyjna (1861-1865); Skonfederowane Stany Ameryki; banknoty i monety Stanów Zjednoczonych; monety greckie i rzymskie; cnota